2022-LBA-751-ESGO Nodal versus peritoneal metastasis on ultrasound. (27th October 2022) - Elagwany, Ahmed
Abstract : Introduction: Granulosa cell tumors are rare ovarian neoplasms and they can metastasize and recur. Due to its rarity, limited data are available on nodal metastasis and recurrence. Recurrence after staging surgery can be nodal or peritoneal related to the lateral pelvic wall. Methods we are aiming here to present a case with a metastatic mass on the lateral pelvic wall and illustrate the differentiation of nodal one versus peritoneal ones. Results: Most cases of granulosa cell tumors are stage I but Unfortunately, they are not benign and can metastasize, recur, and cause death. the detection of extra-ovarian metastasis at initial diagnosis depends on the completeness of surgical exploration/staging. Surgery remains the mainstay of initial management. If Metastasis occur on the Peritoneum or nodes at the lateral pelvic wall, it can be differentiated by compressibility of the iliac vessels, fat plane in between, vasculature of the mass in relation to iliac vessels and connecting vessels in between. Conclusions: Ultrasound can be effective in detecting recurrence on follow up and differentiating between nodal or peritoneal metastasis on lateral pelvic wall.